2017
DOI: 10.1051/matecconf/201713101002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of date palm frond as a fuel for thermal conversion processes

Abstract: Abstract. Date palm fronds (DPF) have similar physical appearances to those of oil palm fronds and coconut palm fronds, which have been reported as having good potential as a source of energy through thermochemical conversion of biomass. However, nearly no report has been found pertaining to thermochemical properties of DPF. Hence, it has remained unclear whether DPF can become suitable feedstock for power generation. This study investigated the characteristics of DPF as a potential solid fuel for heat and pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the current investigation, the calorific value of the feedstock was determined to be 20.33 MJ/kg greater than the value of coal, which is 16.16 MJ/kg 33) . The calorific value of biomass typically falls between 15 and 20 MJ/kg, which is comparable to the calorific value of a low-rank coal 37) . A high value of lignin in given biomass shows the suitability of the biomass to present high calorific value.…”
Section: Proximate Test and Energy Valuementioning
confidence: 97%
See 2 more Smart Citations
“…In the current investigation, the calorific value of the feedstock was determined to be 20.33 MJ/kg greater than the value of coal, which is 16.16 MJ/kg 33) . The calorific value of biomass typically falls between 15 and 20 MJ/kg, which is comparable to the calorific value of a low-rank coal 37) . A high value of lignin in given biomass shows the suitability of the biomass to present high calorific value.…”
Section: Proximate Test and Energy Valuementioning
confidence: 97%
“…A high value of lignin in given biomass shows the suitability of the biomass to present high calorific value. Lignin is the hardest to thermally decompose and contain the highest amount of energy in a biomass 37) . The energy content of the feedstock material of this study was found to be higher than the values of all the biomass presented in Table 1 including coal, except date palm seed and palm kernel shell (PKS).…”
Section: Proximate Test and Energy Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the ultimate and proximate analysis of the biomass listed from India [24][25][26][27][28][29]. The average LHV of woody biomass is reported to be 15,435 kJ/kg at dry condition.…”
Section: Biomass Resourcementioning
confidence: 99%
“…By the end of 2023, studies on new types of biomass as alternative co-firing fuel were conducted on a laboratory-scale. This includes characterization of palm frond and stem biomass (Sadig et al, 2017;Umar et al, 2020) and cofiring wet hog-sludge fuel with coal in combustion tests, which contribute to higher sulfur dioxide emission (Laursen & Grace, 2002) or direct co-firing testing at CFPP.…”
Section: Introductionmentioning
confidence: 99%